Systematic evaluation of molecular genetic, morphological and acoustic variation reveals three species in the Litoria revelata complex (Anura: Pelodryadidae) - Price, Luke C.; Hoskin, Conrad J.; Mahony, Michael J.; Donnellan, Stephen C. (Zootaxa, 2025)
We used a combination of nuclear and mitochondrial genetic data, body measurements and colouration, and male advertisement calls to analyse the systematic implications of variation in the whirring treefrog Litoria revelata complex, which occurs in three allopatric populations—north-eastern New South Wales/south-eastern Queensland, mid-eastern Queensland, and northern Queensland. The three populations each form divergent lineages for both the nuclear (single nucleotide polymorphisms; SNP) and mitochondrial datasets and are diagnosable also on the basis of morphology and advertisement calls. In combination, we use these lines of data to recognise three species: L. revelata in north-eastern New South Wales/south-eastern Queensland, L. eungellensis sp. nov. in mid-eastern Queensland, and the resurrected L. corbeni in northern Queensland. We provide a preliminary conservation assessment for each species, with the latter two species being localised to very small upland areas and warranting conservation listing and attention.